Community Based Marketing and Customer Live Time Value: an Analysis on Their Potential for Improving the Economy of East Java Province - Andriani Kusumawati; Srikandi Kumadji; Devi Farah Azizah (e-2477-1929)
The purpose of this study was to analyse the typology and factors determining the formation of customer communities, to know the patterns and forms of costumer communities, and to examine product penetration to customer communities in East Java province. This study uses a mixed method research with exploratory approach. A qualitative approach is used to find answers to the objectives of the study. Typology of communities based on factors forming the communities can be due to similarities in brand or product consumed. Product penetration in each community can be done without any intervention or direct relationship with the company. The relationship between companies and communities can be divided into three forms. First, companies do not undertake any relationship with communities. Second, companies provide sponsorship and assistance for community activities incidentally. Third, companies build continuous collaboration with communities to organize joint activities. Quantitative testing of the 16 (sixteen) hypotheses shows that only 6 (six) hypotheses are supported by this study model. These results are expected to represent the contribution of Community Based Marketing in improving the Customer Lifetime Value and its implications for the economy of East Java Province.